The "making" of world-class athletes is still a case for humble admissions - Beneke, R. (International Journal of Sports Physiology and Performance, 2023)
Talent is defined as the natural ability to be good at something, especially without being taught. Talent is a rare quality and essential for excellent performance. Nevertheless, there seems to be conventional wisdom that world-class athletes are always "made" not born. The "making" of world-class performance often requires sports with a large participant base and extensive sport-specific deliberate practice. These requirements impose a circular process of sequential identification, development, and selection.